2002
DOI: 10.18356/32dfc431-en
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour related to HIV/AIDs: Commercial sex and condom use in Hanoi, Viet Nam

Abstract: Globally, 40 million adults and children were living with HIV (human immunodeficiency virus)/AIDS (acquired immunodeficiency syndrome) at the end of 2001. Of infected adults, 48 per cent were women. In 2001, the global

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…A study in Hanoi in 2002 indicated that one-third of males aged 18–55 had ever had sex with a FSW; among that one-third, 45.3% had visited FSW more than five times in their life. Additionally, only 36.4% reported that they always used a condom with FSW [ 37 ]. This figure was higher among migrant workers, among whom one third reported having had sex with FSW within the preceding 12 months [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study in Hanoi in 2002 indicated that one-third of males aged 18–55 had ever had sex with a FSW; among that one-third, 45.3% had visited FSW more than five times in their life. Additionally, only 36.4% reported that they always used a condom with FSW [ 37 ]. This figure was higher among migrant workers, among whom one third reported having had sex with FSW within the preceding 12 months [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nepal's poverty, political instability, and gender inequality, combined with low levels of education, make the task all the more challenging, as well as the denial, stigma, and discrimination that surround HIV and AIDS [50]. Detailed information on sexual health behavior and knowledge and reduced premarital and extramarital sexual activity are considered as the most preventive measures for the spread of STIs/HIV/AIDS [53,56].…”
Section: Young People and The Hiv/aids Epidemicmentioning
confidence: 99%
“…Although they do not wish to get pregnant, studies have highlighted that few women engaging in sexual relations use contraceptive methods -or use them incorrectly or inconsistently. Generally, there is a belief that contraceptives are for married couples who do not wish to have more children than they already do (Bélanger & Hong 1999, Nguyen Minh Thang et al 2002.…”
Section: Women's Sexuality and Abortionmentioning
confidence: 99%